2005
DOI: 10.1097/01.mco.0000165011.69943.39
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis in clinical practice: a new perspective on its use beyond body composition equations

Abstract: The phase angle can be considered a global marker of health, and future studies are needed to prove its utility in intervention studies. Bioelectrical impedance vector analysis has increased its utility in clinical practice, even when the equations may be inaccurate for body composition analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
282
0
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(321 citation statements)
references
References 50 publications
6
282
0
19
Order By: Relevance
“…On the other hand, more interesting results emerged for phase angle. This BIA variable is thought to be due in vivo to the capacitance of cell membranes and tissue interfaces and therefore to be related to body cell mass (Barbosa-Silva and Barros, 2005). From a nutritional viewpoint, phase angle is decreased in different forms of undernutrition and is a predictor of survival in several pathological conditions (Barbosa-Silva and Barros, 2005;Bellizzi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more interesting results emerged for phase angle. This BIA variable is thought to be due in vivo to the capacitance of cell membranes and tissue interfaces and therefore to be related to body cell mass (Barbosa-Silva and Barros, 2005). From a nutritional viewpoint, phase angle is decreased in different forms of undernutrition and is a predictor of survival in several pathological conditions (Barbosa-Silva and Barros, 2005;Bellizzi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…BIA is utilised in a range of clinical conditions to routinely measure body composition. Clinical trials have shown the use of BIA as a non-invasive diagnostic tool to evaluate nutritional status, determine the prognosis of clinical patients, and evaluate the influence of therapeutic agents in disease management 7,[11][12][13] .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…29 Bioelectrical impedance analysis is useful in assessing and monitoring nutritional status. 15,30 The phase angle, one of the raw data obtained from bioelectrical impedance analysis measurements and therefore independent from the equipment and internal algorithms used, has proved to be a good prognostic, nutritional and membrane cell function marker in various diseases. 18,21,31,32 Sex-, age-and BMI-specific reference values of the phase angle from a large healthy German population 33 34 The transformation of phase angle values into standardized values (Z-score) allows us to quantify individual deviations from sex-, age-and BMI-specific population averages and to compare subjects from a heterogeneous group.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…The phase angle is one of them. It is measured by bioelectrical impedance analysis and reflects cell membrane function 15 and indirectly, the body's muscle mass. 16 It is an established parameter for diagnosing malnutrition, and a useful prognostic marker in many clinical conditions 17 including several types of cancer.…”
Section: Introductionmentioning
confidence: 99%